2019
DOI: 10.5713/ajas.18.0538
|View full text |Cite
|
Sign up to set email alerts
|

Potential crosstalk of oxidative stress and immune response in poultry through phytochemicals — A review

Abstract: Phytochemicals which exist in various plants and fungi are non-nutritive compounds that exert numerous beneficial bioactive actions for animals. In recent years following the restriction of antibiotics, phytochemicals have been regarded as a primal selection when dealing with the challenges during the producing process in the poultry industry. The selected fast-growing broiler breed was more fragile when confronting the stressors in their growing environments. The disruption of oxidative balance that impairs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 93 publications
1
52
0
Order By: Relevance
“…For broilers, inflammation is a double-edged sword depending of its level [11]. Lee et al [30] indicated that LPS challenge on broilers (1 mg/kg body weight) causes significant weight loss because of the immune response and decrease in feed intake. In broilers, there are two ways to decrease the inflammation level: one is to decrease the stimulants, such as LPS or bacterial toxin, and the other way is to block the pro-inflammatory cytokine pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For broilers, inflammation is a double-edged sword depending of its level [11]. Lee et al [30] indicated that LPS challenge on broilers (1 mg/kg body weight) causes significant weight loss because of the immune response and decrease in feed intake. In broilers, there are two ways to decrease the inflammation level: one is to decrease the stimulants, such as LPS or bacterial toxin, and the other way is to block the pro-inflammatory cytokine pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data indicate that Nrf2 activation is one of the most important mechanisms of phytochemical protective effects in poultry and farm animals [91,286,287]. Dietary inclusion of Antrodia cinnamomea (a medical fungus) powder into the broiler diet at 0.1-0.4% for 35 days was shown to increase Nrf2 expression in the liver [288].…”
Section: Phytochemicalsmentioning
confidence: 99%
“…The immunostimulating activities of many of these components have been most widely studied in chicken and human cell lines. 18 Embryonated eggs inoculated with a mixture of NDV or AIV H5N1 with each sample separately affect the virus titer (Tables 3 and 4 37 The macerated whole plant of E. unispina N.E.Br. and the stems of E. poissonii Pax.…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of immunostimulants is one solution to improve the immunity of animals and to decrease their susceptibility to infectious diseases. 18 The use of plant products as immunostimulants has a traditional history. Emerging evidence indicates that herbal remedies and/or natural products exert their beneficial effects on animal immune system mostly by plant secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%